Decadron, Diamox, and Zantac: A Novel Combination for Ventricular Shunt Failure in Pediatric Neurosurgical Patients. Issue 12 (14th December 2021) - Lang, Shih-Shan; Ploof, Jillian; Atkin, Natalie J.; Tran-Du, Kella; Kanuga, Bhavya M.; Storm, Phillip B.; Heuer, Gregory; Yuan, Ian; Abend, Nicholas S.; Kirschen, Matthew P.; Topjian, Alexis A.; Li, Yimei; et al.
Abstract : Objective: Cerebral ventricular shunt failure is common and presents with symptoms that range from headaches to death. The combination of Diamox (acetazolamide), Decadron (dexamethasone), and Zantac (ranitidine) (DDZ) is used at our institution to medically stabilize pediatric patients presenting with symptomatic shunt failure before shunt revision. We describe our experience of this drug combination as a temporizing measure to decrease symptoms associated with shunt failure. Methods: We performed a single-center retrospective chart review of patients younger than 18 years with ventricular shunt failure who underwent a shunt revision between January 2015 to October 2017 and received DDZ before surgery. The outcome variables evaluated included pre-DDZ and post-DDZ clinical symptoms, pain scores, and vital signs. Results: There were 112 cases that received DDZ before shunt revision. The 4 most commonly reported symptoms were analyzed. Headache was observed in 42 cases pre-DDZ, and post-DDZ there was a 71% reduction in headache ( P < 0.0001); emesis was reported pre-DDZ in 76 cases, and post-DDZ there was an 83% reduction ( P < 0.0001); irritability was noted pre-DDZ in 30 cases, and post-DDZ there was a 77% reduction ( P = 0.0003); lethargy pre-DDZ was observed in 60 cases, and post-DDZ 73% demonstrated improvement ( P < 0.0001). Maximum pain scores significantly decreased post-DDZ ( P < 0.0001). Heart rate, systolic, and diastolic blood pressures significantly decreased post-DDZ ( P < 0.0001, P < 0.0001, P = 0.0002, respectively). Conclusions: The combination of Decadron, Diamox, and Zantac is a novel treatment for ventricular shunt failure that may temporarily improve symptoms in patients awaiting shunt revision. Future studies could compare efficacy with other medical treatments.